To TDE or not to TDE: the luminous transient ASASSN-18jd with TDE-like and AGN-like qualities. Issue 2 (4th April 2020) - Neustadt, J M M; Holoien, T W-S; Kochanek, C S; Auchettl, K; Brown, J S; Shappee, B J; Pogge, R W; Dong, Subo; Stanek, K Z; Tucker, M A; Bose, S; Chen, Ping; et al.
ABSTRACT: We present the discovery of ASASSN-18jd (AT 2018bcb), a luminous optical/ultraviolet(UV)/X-ray transient located in the nucleus of the galaxy 2MASX J22434289–1659083 at z = 0.1192. Over the year after discovery, Swift UltraViolet and Optical Telescope (UVOT) photometry shows the UV spectral energy distribution of the transient to be well modelled by a slowly shrinking blackbody with temperature T 2.5 × 10^4 K, a maximum observed luminosity of L_max = 4.5^+0.6_-0.3× 10^44 erg s^-1, and a radiated energy of E = 9.6^+1.1_-0.6 × 10^51 erg . X-ray data from Swift X-Ray Telescope (XRT) and XMM–Newton show a transient, variable X-ray flux with blackbody and power-law components that fade by nearly an order of magnitude over the following year. Optical spectra show strong, roughly constant broad Balmer emission and transient features attributable to He ii, N iii–v, O iii, and coronal Fe. While ASASSN-18jd shares similarities with tidal disruption events (TDEs), it is also similar to the newly discovered nuclear transients seen in quiescent galaxies and faint active galactic nuclei (AGNs).